RECONCILIATION IN IMPLICATURES: DIVERGENCE OF LANGUAGE USE IN DIALOGUES - Singh, Lourembam Surjit (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This paper proposes to investigate the theory of Gricean (1975, 1989) Figure of Speech within the framework of conversational implicatures in the dialogues of a very popular Manipuri Radio play. The Gricean figure of speech exploits or flouts the first maxim i.e. known as maxims of quality. In these maxims exploitation, he subsumes metaphor, irony, hyperbole and meiosis into implicatures as particularized implicatures to convey non-literal meaning. At the same time, in the figure of speech, he reconciled the implied meanings through his maxims and sub-maxims.It reveals divergence of meanings in language use, particularly in the study of dialogues in the play. When he reconciled the maxims of quality in various figures of speech, he flouted the maxims of truthfulness.